Mapping Multiple Intelligences of 7th Grade Junior High School Students: A Study Based on Paulus Winarto's Talent Test and Howard Gardner's Theory - Nadia Wardah Mumtazah; Nurul Bayyinah; Fitri Nur Asanti (South Sulawesi Education Development (SSED), 2025)
This study aims to map the multiple intelligences profile of seventh-grade junior high school students based on Paulus Winarto's Talent Test and Howard Gardner's multiple intelligences theory. The research employs a descriptive quantitative approach with a purposive sample of 30 students. Multiple intelligence data were analyzed based on the overall intelligence average category (high, medium, low), dominant intelligence, and non-dominant intelligence in each category. Results reveal that most students (60%) fall into the medium category, with musical intelligence as the most prominent. Meanwhile, 23% of students are in the high category, dominated by interpersonal and naturalist intelligences. Additionally, 17% of students are in the low category, with logical-mathematical intelligence frequently appearing as non-dominant. These findings highlight the importance of personalized learning approaches to optimize students' dominant intelligences and develop their non-dominant ones. Learning strategies emphasizing exploration, collaboration, and multisensory activities are recommended to support holistic student development.